2017
DOI: 10.1093/ejcts/ezx150
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant repair for mild aortic insufficiency and continuous-flow left ventricular assist devices

Abstract: AI progression among CF-LVAD-supported patients with baseline mild AI is highly prevalent. Baseline aortic root diameter may help identify patients with 'borderline' AI lesion needing repair at device insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Previous studies investigating the association between survival and AoV procedures reported conflicting results, with some studies indicating worse survival, 15–18 whereas others reported similar or better survival rates in patients with a concomitant AoV procedure 19–23 . However, most of these reports referred to single‐centre studies and were limited by lower numbers of patients undergoing a concomitant AoV procedure (only one study included more than 100 patients with an AoV procedure), and some reported only outcomes of multiple concomitant cardiac procedures combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating the association between survival and AoV procedures reported conflicting results, with some studies indicating worse survival, 15–18 whereas others reported similar or better survival rates in patients with a concomitant AoV procedure 19–23 . However, most of these reports referred to single‐centre studies and were limited by lower numbers of patients undergoing a concomitant AoV procedure (only one study included more than 100 patients with an AoV procedure), and some reported only outcomes of multiple concomitant cardiac procedures combined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the association between survival and AoV procedures reported conflicting results, with some studies indicating worse survival, [15][16][17][18] whereas others reported similar or better survival rates in patients with a concomitant AoV procedure. [19][20][21][22][23] However, most of these reports referred to single-centre studies and were limited by lower numbers of patients undergoing a concomitant AoV procedure (only one study included more than 100 patients with an AoV procedure), and some reported only outcomes of multiple concomitant cardiac procedures combined. 15 In the INTERMACS study, patients undergoing a concomitant AoV procedure had significantly lower 1-year survival rates (79% in patients undergoing AoV repair, 72% in patients undergoing AoV replacement and 64% in patients undergoing AoV closure) compared with patients without an AoV procedure (81%) (P = 0.0003).…”
Section: Early and Late Survivalmentioning
confidence: 99%
“…20 In this study, aortic valve closure was associated with the highest mortality rates, and aortic valve repair was associated with the highest incidence of AI progression. Fukuhara and colleagues 21 reported that concomitant aortic valve repair for patients with mild AI pre-LVAD reduced the incidence of moderate or greater AI after the LVAD implantation, although the procedure had no significant impact on survival when compared with the patients with uncorrected mild AI. In this study, post-LVAD functional data were not reported.…”
Section: Surgical Intervention For Pre-left Ventricular Assist Device Aortic Insufficiencymentioning
confidence: 99%
“…Consequently, greater than mild AI is generally considered an indication for intervention on the aortic valve (AV) at the time of LVAD implantation [3]. The options for intervention include patch occlusion, AV repair, or replacement with a bioprosthetic valve [1, 4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The central coaptation repair stitch (Park’s stitch) has been shown to be efficacious in decreasing AI in the short term [710]. A retrospective assessment at a single center found the two year results of the Park’s stitch is acceptable with decreased AI compared to patients that did not receive AV repair [4]. This technique has advantages of a relatively short cross-clamp time and no significant added expense.…”
Section: Introductionmentioning
confidence: 99%